Development of Teaching Materials for Multicultural Education Literacy in Integrating Baduy Tribal Culture in International Elementary Schools - Khusnun A'nillah; Bambang Yulianto; Suhartono Suhartono (Lembaga Penjaminan Mutu, IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2024)
This research aims to develop multicultural education literacy teaching materials that integrate the culture of the Baduy Tribe in International Elementary Schools using the ADDIE method. In this era of globalization, multicultural education is becoming increasingly important to strengthen national identity and promote cultural diversity. The Baduy tribe, with its rich culture, significantly contributes to Indonesia's cultural heritage. Therefore, integrating Baduy culture into the curriculum is expected to enrich students' learning experience. The research method used is the ADDIE method, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. At the development stage, teaching materials are created and integrated with the cultural elements of the Baduy Tribe. Implementation is done by testing the teaching materials on grade IV students of International Elementary School. Evaluation was conducted to measure the effectiveness of teaching materials in improving students' understanding of multicultural literacy.. The evaluation also shows that students can better appreciate cultural diversity after using this teaching material. Constraints encountered during development and implementation include limited resources and time, but they can be overcome with collaborative strategies and schedule adjustments. In conclusion, the development of multicultural education literacy teaching materials that integrate the culture of the Baduy Tribe using the ADDIE method has succeeded in improving the quality of learning at SD International. Recommendations for future research are to expand the scope of other local cultures and test the effectiveness of teaching materials over a longer period.